2014
DOI: 10.1002/smll.201303633
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles (MSNs) for Detoxification of Hazardous Organophorous Chemicals

Abstract: The study reports the effect of mesoporous silica nanoparticles (MSNs) on detoxification of toxic organophorous compounds. Based on gravimetric sensing experiment with resonant microcantilever, rapid adsorption of the organophorous simulant of dimethyl methylphosphonate (DMMP) onto MSNs is confirmed. The experimentally observed irreversible gravimetric-signal implies that substitution-reaction possibly occurs at the nanomaterial surface. By exploring a method of gravimetric detection at different temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…The FT-IR spectrum of the SiO 2 -TiO 2 is used to investigate the composition and structure of the resultant samples [38][39][40]. As shown in Fig.…”
Section: Structure and Characterization Of Carriersmentioning
confidence: 99%
“…The FT-IR spectrum of the SiO 2 -TiO 2 is used to investigate the composition and structure of the resultant samples [38][39][40]. As shown in Fig.…”
Section: Structure and Characterization Of Carriersmentioning
confidence: 99%
“…Although some special coating techniques like ink-jet spotting and tiny-capillary incubation under optical microscope have been used, manual loading is really a difficult task to secure uniform sensing performance within a whole run of fabricated sensors [13,[19][20][21][22]. In our lab, a commercially available micro-manipulator equipped with a labmade capillary is employed to load the sensing material onto the desired micro-region of the cantilever [23][24][25][26][27][28][29]. With the help of this special tool, various sensing materials like functionalized mesoporous silica, sensing polymer and Au-NPs/grapheme-oxide hybrid have been precisely coated onto resonant cantilevers to construct high-sensitivity gas sensors [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In our lab, a commercially available micro-manipulator equipped with a labmade capillary is employed to load the sensing material onto the desired micro-region of the cantilever [23][24][25][26][27][28][29]. With the help of this special tool, various sensing materials like functionalized mesoporous silica, sensing polymer and Au-NPs/grapheme-oxide hybrid have been precisely coated onto resonant cantilevers to construct high-sensitivity gas sensors [23][24][25][26][27][28][29]. Unfortunately, such an approach is still a one-by-one method that suffers from several drawbacks like time-consuming, labor-intensive, inconsistent and irreproducible.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that adsorbing-type materials tend to spontaneously adsorb molecules to lower the surface-energy, and the adsorbed molecule amount will decrease with temperature increasing [1]. When the temperature reaches a certain limit, adsorption will stop.…”
Section: Introductionmentioning
confidence: 99%
“…The previous reports indicated that silica with ≡Si-OH covered on its surface is sensitive to DMMP-vapor (dimethyl-methylphosphonate, a simulant for toxic organophosphorus-agents) [1][2][3]. Based on the adsorption between mesoporous silica nanoparticles (MSNs) and organophosphorus, MSNs shows potential for developed as toxic organophosphorus detoxification materials.…”
Section: Introductionmentioning
confidence: 99%